2002
DOI: 10.1177/00222194020350040801
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Academic Self-Evaluations in Adolescents with Learning Disabilities

Abstract: The purpose of this study was to document the degree of overestimation of academic skills among students with learning disabilities (LD) and to evaluate the role of reference group and metacognitive awareness in such overestimation. High school students with (n = 52) and without (n = 49) LD in Grades 9 through 12 completed a self-concept scale and a survey requiring them to rate their own academic skills in 17 specific skill areas. Students were further asked to predict their performance on two academic tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 36 publications
8
107
0
9
Order By: Relevance
“…However, reports by the researchers do not all point in the same direction. Thus, whereas one group of studies has shown that students with LD presented lower ability and achievement expectations than their counterparts without LD (Bear, Juvonen, & McInerney, 1993;Chapman, 1988;Gans, Kenny, & Ghany, 2003;González-Pienda et al, 2000;Grolnick & Ryan, 1990;Harter, Whitesell, & Junkin, 1998;Kloomok & Cosden, 1994;Núñez et al, 1995;Rogers & Saklofske, 1985;Stone & May, 2002;Valas, 1999;Vaughn, Elbaum, Schumm, & Hughes, 1998;Vaughn, Haager, Hogan, &Kouzekanani, 1992), another group of studies found no differences in academic self-concept between students with and without LD (Bear & Minke, 1996;Bear, Minke, Griffin, & Deemer, 1998;Dyson, 2003;Meltzer & Montague, 2001;Meltzer, Roditi, Houser, & Perlman, 1998;Montague & van Garderen, 2003;Pintrich, Anderman, & Klobucar, 1994;Priel & Leshem, 1990). With regard to general self-concept, the data provided by past research are more concurrent.…”
Section: Self-conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reports by the researchers do not all point in the same direction. Thus, whereas one group of studies has shown that students with LD presented lower ability and achievement expectations than their counterparts without LD (Bear, Juvonen, & McInerney, 1993;Chapman, 1988;Gans, Kenny, & Ghany, 2003;González-Pienda et al, 2000;Grolnick & Ryan, 1990;Harter, Whitesell, & Junkin, 1998;Kloomok & Cosden, 1994;Núñez et al, 1995;Rogers & Saklofske, 1985;Stone & May, 2002;Valas, 1999;Vaughn, Elbaum, Schumm, & Hughes, 1998;Vaughn, Haager, Hogan, &Kouzekanani, 1992), another group of studies found no differences in academic self-concept between students with and without LD (Bear & Minke, 1996;Bear, Minke, Griffin, & Deemer, 1998;Dyson, 2003;Meltzer & Montague, 2001;Meltzer, Roditi, Houser, & Perlman, 1998;Montague & van Garderen, 2003;Pintrich, Anderman, & Klobucar, 1994;Priel & Leshem, 1990). With regard to general self-concept, the data provided by past research are more concurrent.…”
Section: Self-conceptmentioning
confidence: 99%
“…With regard to general self-concept, the data provided by past research are more concurrent. Specifically, McPhail and Stone (1995) have reviewed the most relevant studies and have presented data indicating that students with LD generally show positive general self-concepts and perceive themselves to be as capable as their peers (e.g., Bear, Clever, & Proctor, 1991;Bear et al, 1993;Dyson, 2003;Gans et al, 2003;Harter et al, 1998;Nowicki, 2003;Sabornie, 1994;Stone & May, 2002;Valas, 1999).Researchers have formulated various explanations for these apparently contradictory data regarding academic self-concept. The most frequently proposed hypotheses were the following: (1) students with LD make unrealistic assessments of their abilities because of metacognitive deficits that limit their capacity to reflect upon their own abilities (Montague & van Garderen, 2003;Stone & May, 2002); (2) perception of social acceptance and favorable feedback by others (teachers, parents, friends); (3) lack of effort and engagement in school tasks, which allows these students to attribute failures to lack of effort (Bear et al, 1991;Kloomok & Cosden, 1994); and (4) the development of disruptive behaviors as a way to avoid questioning one's own ability (Covington, 1998).…”
mentioning
confidence: 99%
“…Las actitudes y expectativas de la sociedad determinan el grado hasta el cual las personas con SD pueden aprender, desarrollar, amar, vivir o trabajar. Aunque la inclusión, por lo menos como filosofía, se ha vuelto ampliamente aceptada (FARIA;GILSON;COOKE;MAHONEY, 2005;STONE;MAY, 2002), la aceptación total de las personas con SD bien pareciera no haberse logrado aún. Hacia esta clarificación camina este trabajo, en concreto centrando nuestra atención en la percepción que de ellos tienen los futuros maestros, por tratarse de un cuerpo profesional que, a corto o medio plazo, tendrán que dedicar su ejercicio laboral para con este grupo de población.…”
Section: The Social Perception Of People With Down Syndrome: the Epsdunclassified
“…Der PIB wurde bisher in der Altersgruppe von 7-13 Jahren untersucht (Owens et al, 2007), ohne dass sich dabei Alterseffekte gezeigt hätten (Owens & Hoza, 2003 (Stone & May, 2002). Weitere Forschung ist notwendig, um festzustellen, ob und wann ein PIB eine positive Schutzfunktion hat oder sich eher negativ auf die schulische Leistungsentwicklung auswirkt (Owens et al, 2007 (Marsh, 1989 Studien zeigen, dass Kinder mit ADHS sich besonders in dem Bereich überschätzen, in dem sie die größten Defizite haben (Hoza et al 2002(Hoza et al , 2004 Rohwertpunkten festgelegt (Huss, et al, 2008;Woerner et al, 2002 (Guay et al, 2003;Marsh & Craven, 2006).…”
Section: Ursachen Des Positive Illusory Biasunclassified